ROLE OF CIVIL SOCIETY ORGANIZATIONS IN POST CONFLICT ENVIRONMENT - IGBO, Mercy Chinyelu (Socialscientia: Journal of Social Sciences and Humanities, 2020)
The aftermath of any violent conflict is devastation, depression, degradation and ruins. This paper examines the role civil society organisations plays in lifting these burdens from survivors or victims of the conflicts. The objective is to understand the positive impact of these roles in rebuilding, reconstructing and rehabilitating people affected by conflict and then identify gaps and ways to improve efficiency and effectiveness in carrying out these responsibilities. Aided with the use of secondary data/content analysis it argues that political insecurity, violent extremism and state collapse are products of long term degenerative politics marked by a loss of control over economic and political space. Conclusively government alone cannot handle post conflict reconstruction, capacity building, economic development, peace-building etc. it does not also have the capacity to access interventionist funds/aids from international donors and agencies. The civil society organisations can access these funds; this will enable them play these paramount roles so they should be highly supported.